Growth rate mediates hidden developmental plasticity of female yellow dung fly reproductive morphology in response to environmental stressors. Issue 1 (24th January 2022) - Walters, Richard J.; Berger, David; Blanckenhorn, Wolf U.; Bussière, Luc F.; Rohner, Patrick T.; Jochmann, Ralf; Thüler, Karin; Schäfer, Martin A.
Abstract: Understanding how environmental variation influences even cryptic traits is important to clarify the roles of selection and developmental constraints in past evolutionary divergence and to predict future adaptation under environmental change. Female yellow dung flies ( Scathophaga stercoraria ) typically have three sperm storage compartments (3S), but occasionally four (4S). More spermathecae are thought to be a female adaptation facilitating sperm sorting after mating, but the phenotype is very rare in nature. We manipulated the flies' developmental environment by food restriction, pesticides, and hot temperatures to investigate the nature and extent of developmental plasticity of this trait, and whether spermatheca expression correlates with measures of performance and developmental stability, as would be expected if 4S expression is a developmental aberration. The spermathecal polymorphism of yellow dung fly females is heritable, but also highly developmentally plastic, varying strongly with rearing conditions. 4S expression is tightly linked to growth rate, and weakly positively correlated with fluctuating asymmetry of wings and legs, suggesting that the production of a fourth spermatheca could be a nonadaptive developmental aberration. However, spermathecal plasticity is opposite in the closely related and ecologically similar Scathophaga suilla, demonstrating that overexpression of spermathecae under developmental stress is not universal. At the same time, we found overall mortality costs as well as benefits of 4S pheno‐ and genotypes (also affecting male siblings), suggesting that a life history trade‐off may potentially moderate 4S expression. We conclude that the release of cryptic genetic variation in spermatheca number in the face of strong environmental variation may expose hidden traits (here reproductive morphology) to natural selection (here under climate warming or food augmentation). Once exposed, hidden traits can potentially undergo rapid genetic assimilation, even in cases when trait changes are first triggered by random errors that destabilize developmental processes. Abstract : Female yellow dung flies ( Scathophaga stercoraria ) express 3 or 4 sperm storage organs, the related S. suilla 2 or 3 (right). Is this a developmental aberration, or an adaptive trait for sperm sorting? Environmental change (heat, pesticides, abundant food) augments developmental errors and induces spermathecal variation in proportion to growth rate, which can expose previously hidden traits to natural selection to produce a new beneficial function. Highlights: Female yellow dung flies naturally vary in number of sperm storage compartments (3S or 4S). This spermathecal polymorphism is strongly heritable but also developmentally plastic. 4S expression is linked to growth rate and weakly correlated with fluctuating asymmetry, so potentially a developmental aberration. There are mortality costs as well as benefits for 4S phenotypes, suggesting adaptive life‐history trade‐offs. Spermathecal plasticity differs in the closely related and ecologically similar Scathophaga suilla . Environmental changes can expose hidden traits with initially no function to natural selection.